2023
DOI: 10.1080/07853890.2023.2231342
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of breast cancer patients with bone metastasis could be potentially estimated based on blood routine test and biochemical examination at admission

Abstract: Purpose Due to the poor and unpredictable prognosis of breast cancer (BC) patients with bone metastasis, it is necessary to find convenient and available prognostic predictors. This study aimed to recognize the clinical and prognostic factors related to clinical laboratory examination and to construct a prognostic nomogram for BC bone metastasis. Methods We retrospectively analyzed 32 candidate indicators from clinical features and laboratory examination data of 276 BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Some hematological markers, such as inflammatory index and red blood cell distribution width, have obvious advantages in predicting prognosis ( 20 22 ). Inflammation plays a crucial regulatory role in the development of breast cancer ( 23 ), and hematological biomarkers can provide valuable clues about pathophysiological changes ( 24 , 25 ). Research has shown that a higher lymphocyte proportion is positively correlated with a favorable prognosis ( 26 ), whereas a lower percentage of eosinophils ( 27 ), higher red blood cell distribution width ( 28 ), and higher platelet large cell ratio ( 29 ) are associated with a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Some hematological markers, such as inflammatory index and red blood cell distribution width, have obvious advantages in predicting prognosis ( 20 22 ). Inflammation plays a crucial regulatory role in the development of breast cancer ( 23 ), and hematological biomarkers can provide valuable clues about pathophysiological changes ( 24 , 25 ). Research has shown that a higher lymphocyte proportion is positively correlated with a favorable prognosis ( 26 ), whereas a lower percentage of eosinophils ( 27 ), higher red blood cell distribution width ( 28 ), and higher platelet large cell ratio ( 29 ) are associated with a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, cancer-related thrombosis has become an important basis for the prediction and clinical analysis of breast cancer ( 3 ). A number of blood parameters related to transfusion technology [e.g., TEG ( 34 ), routine blood test ( 35 ), and PLT count ( 36 )] are important in providing effective information during the whole procedure of medical interventions, including tumor screening ( 37 ), risk assessment ( 38 ), and inpatient ( 39 ) and outpatient prevention ( 40 ). Research shows that venous thrombosis is one of the common causes of death in patients with breast cancer ( 41 ).…”
Section: Introductionmentioning
confidence: 99%